The effect of organizational power dynamics on strategic success - Hatef AL-Fatlawy, Meithak; Muhammad Ali al-Shammari, Rafa (Iraqi Journal for Administrative Sciences, 2024)
This study aimed to identify the extent of the impact of the dynamics of organizational power in department heads, administrative and technical officers on the strategic success of employees of the Holy Karbala Traffic Directorate. The dimensions of the organizational power were chosen by six dimensions: (legal power, reward power, experience power, reference power, information power, and coercive power). As a sample, opinion poll was obtained from employees of the Holy Karbala Traffic Directorate, with a total of 107 members. The study adopted the questionnaire as a main tool for obtaining the required data and a set of statistical methods were adopted for data analysis and hypothesis testing. The study reached a set of conclusions, the most important of which is that the administration in the Holy Karbala Traffic Directorate has a high capacity to take advantage of the organizational powers available to them in the Directorate and that they employ them properly, and the positions of individuals indicated that the administration in the Holy Karbala Traffic Directorate has the advantage of a balanced use of the legal power to work in conflict management that arise as a result of work and timekeeping. Individuals in the Holy Karbala Traffic Directorate feel that the administration in the directorate has a serious approach in dealing with awarding bonuses that are appropriate to the type of tasks assigned to them, and the expertise that the departments have in the directorate is important in enhancing the capabilities of individuals in the directorate towards achieving the best levels of work. The administration of the Holy Karbala Traffic Directorate is also characterized by its focus on utilizing the power of information it possesses. The study came out with a set of recommendations, including: the need for the Karbala Traffic Directorate to enhance the individuals’ sense of the importance of its legal force based on the law and its implementation within the framework of the information capacity it possesses, which can achieve strategic success. The reward is considered one of the factors that concern the employees in general and is a highly sensitive topic, especially as it is directly related to the results expected by the Directorate, the need for intellectual, scientific and practical linkage between the Holy Karbala Traffic Directorate and universities, colleges and research centers with a good reputation so that the personnel in the Directorate benefit from the diversification of knowledge of these universities.